Fresno County Bar Association Law Day Luncheon with Keynote Speaker Justice Pauline Davis Hanson - Watkins, Howard::::::::: (1982)
Supervisor Harry Huey, Paula Roberts, Justice Hanson speaking, Fresno County Bar Association President-Elect Doug Jensen The Fresno Hilton signs on lectern